Change the Plan — How Hard Can That Be? - Behnke, Gregor; Höller, Daniel; Bercher, Pascal; Biundo, Susanne (Proceedings of the International Conference on Automated Planning and Scheduling, 2016)
Interaction with users is a key capability of planning systems that are applied in real-world settings. Such a system has to be able to react appropriately to requests issued by its users. Most of these systems are based on a generated plan that is continually criticised by him, resulting in a mixed-initiative planning system. We present several practically relevant requests to change a plan in the setting of hierarchical task network planning and investigate their computational complexity. On the one hand, these results provide guidelines when constructing algorithms to execute the respective requests, but also provide translations to other well-known planning queries like plan existence or verification. These can be employed to extend an existing planner such that it can form the foundation of a mixed-initiative planning system simply by adding a translation layer on top.